Eurytrematosis: an emerging parasitosis in cattle from Northeast Argentina - Pantiu, Andrea Julia; Bischoff, Rubén Darío; Olmos, Leandro Hipolito; Signorini Porchiett, Marcelo Lisandro; Aguirre Castro, Laura Sabrina; Avellaneda Cáceres, Agustín; Micheloud, Juan Francisco (Elsevier, 2025)
This study was carried out in the northwest region of Misiones Province, Argentina, focusing on the clinical, pathological, epidemiological, and parasitological aspects of Eurytrema spp. in cattle. Clinical monitoring of five cattle cases exhibiting chronic weight loss revealed that affected animals had enlarged pancreases, with severe fibrosis and presence of Eurytrema coelomaticum in the pancreatic ducts. Histopathological analysis confirmed severe fibrosing periductal lymphoplasmacytic interstitial pancreatitis with intralesional trematodes. A cross-sectional epidemiological study was conducted from June 2018 to May 2021, involving 44 farms and 718 fecal samples. Coproparasitological analysis revealed a within-farm prevalence of 70.7%, with an animal-level prevalence of 37.5%. A multivariable generalized linear model identified the abundance of snails, the limited availability of monthly veterinary assistance, and loss of body condition as significant risk factors for Eurytrema sp. prevalence. Spatial analysis detected three significant clusters with varying prevalence levels, highlighting areas of high and low parasite occurrence. This study represents the first detailed investigation of Eurytrema sp. in Argentina, confirming its endemic presence in the central-northern region of Misiones Province. The findings underscore the need for further research to evaluate the parasite's spread across the province and its potential impact on livestock production.